Diagnostic performance of the McIsaac score for group A streptococcal pharyngitis in children under three years of age - Pavlović, Momčilo; Berenji, Karolina; Rokvić, Željko; Ilić, Tatjana (Vojnosanitetski pregled, 2026)
Background/Aim. Group A β-hemolytic streptococcus (GAS) pharyngitis most commonly affects school-aged children. The aim of this study was to assess the effectiveness and clinical applicability of the McIsaac score for diagnosing GAS pharyngitis in children under 3 years of age. Methods. The retrospective study included a total of 282 children under 3 years of age diagnosed with acute pharyngitis in a pediatric outpatient setting in Subotica, Serbia, between September 2023 and August 2024. Data on demographic and clinical characteristics were collected, including McIsaac score values. The obtained results were analyzed in relation to rapid antigen detection test (RADT) findings, which were performed on all children. Results. Of the total 282 children, 143 (50.7%) were RADT-positive. The McIsaac score demonstrated limited diagnostic accuracy, with sensitivity and specificity values for scores 0–2 of 69.9% and 38.1%, respectively, and for scores 3–4 of 30.7% and 61.9%, respectively. Receiver operating characteristic (ROC) curve analysis yielded an area under the curve (AUC) of 0.561. The absence of cough was the only individual McIsaac criterion significantly associated with a positive RADT result. Conclusion. The McIsaac score alone has limited effectiveness in identifying GAS pharyngitis in children under 3 years of age. Given the substantial symptom overlap between bacterial and viral infections in this age group, additional diagnostic methods are necessary to improve diagnostic accuracy.
Keywords: child, preschool; diagnosis; infant; pharyngitis; rapid diagnostic tests; streptococcus pyogenes.